Activated factor X targeted stored in platelets as an effective gene therapy strategy for both hemophilia A and B. Issue 3 (24th March 2021) - Wang, Dawei; Shao, Xiaohu; Wang, Qiang; Pan, Xiaohong; Dai, Yujun; Yao, Shuxian; Yin, Tong; Wang, Zhugang; Zhu, Jiang; Xi, Xiaodong; Chen, Zhu; Chen, Saijuan; et al.
Abstract: Background: Treatment of hemophiliacs with inhibitors remains challenging, and new treatments are in urgent need. Coagulation factor X plays a critical role in the downstream of blood coagulation cascade, which could serve as a bypassing agent for hemophilia therapy. Base on platelet‐targeted gene therapy for hemophilia by our and other groups, we hypothesized that activated factor X (FXa) targeted stored in platelets might be effective in treating hemophilia A (HA) and B (HB) with or without inhibitors. Methods: To achieve the storage of FXa in platelets, we constructed a FXa precursor and used the integrin αIIb promoter to control the targeted expression of FXa precursor in platelets. The expression cassette (2bFXa) was carried by lentivirus and introduced into mouse hematopoietic stem and progenitor cells (HSPCs), which were then transplanted into HA and HB mice. FXa expression and storage in platelets was examined in vitro and in vivo. We evaluated the therapeutic efficacy of platelet‐stored FXa by tail bleeding assays and the thrombelastography. In addition, thrombotic risk was assessed in the recipient mice and the lipopolysaccharide induced inflammation mice. Results: By transplanting 2bFXa lentivirus‐transduced HSPCs into HA and HB mice, FXa was observed stably stored in platelet α‐granules, the stored FXa is releasable and functional upon platelet activation. The platelet‐stored FXa can significantly ameliorate bleeding phenotype in HA and HB mice as well as the mice with inhibitors. Meanwhile, no FXa leakage in plasma and no signs of increased risk of hypercoagulability were found in transplantation recipients and lipopolysaccharide induced septicemia recipients. Conclusions: Our proof‐of‐principle data indicated that target expression of the FXa precursor to platelets can generate a storage pool of FXa in platelet α‐granules, the platelet‐stored FXa is effective in treating HA and HB with inhibitors, suggesting that this could be a novel choice for hemophilia patients with inhibitors. Abstract : Target expression of the FXa precursor to platelets can generate a storage pool of FXa in platelet α‐granules. The platelet‐delivered FXa is effective in ameliorating the hemorrhagic phenotype of both HA and HB murine models, even in the presence of inhibitors. No sign of hypercoagulability was found in platelet FXa‐containing mice under either steady or pathological status.